The Proatherogenic Effect of Chronic Nitric Oxide Synthesis Inhibition in ApoE-Null Mice Is Dependent on the Presence of PPARα. (22nd January 2014) - Vechoropoulos, Michal; Ish-Shalom, Maya; Shaklai, Sigal; Sack, Jessica; Stern, Naftali; Tordjman, Karen M.
Abstract : Inhibition of endothelial nitric oxide synthase (eNOS) accelerates atherosclerosis in ApoE-null mice by impairing the balance between angiotensin II (AII) and NO. Our previous data suggested a role for PPAR α in the deleterious effect of the renin-angiotensin system (RAS). We tested the hypothesis that ApoE-null mice lacking PPAR α (DKO mice) would be resistant to the proatherogenic effect of NOS inhibition. DKO mice fed a Western diet were immune to the 23% worsening in aortic sinus plaque area seen in the ApoE-null animals under 12 weeks of NOS inhibition with a subpressor dose of L-NAME, P = 0.002 . This was accompanied by a doubling of reactive oxygen species (ROS-) generating aortic NADPH oxidase activity (a target of AII, which paralleled Nox1 expression) and by a 10-fold excess of the proatherogenic iNOS, P < 0.01 . L-NAME also caused a doubling of aortic renin and angiotensinogen mRNA level in the ApoE-null mice but not in the DKO, and it upregulated eNOS in the DKO mice only. These data suggest that, in the ApoE-null mouse, PPAR α contributes to the proatherogenic effect of unopposed RAS/AII action induced by L-NAME, an effect which is associated with Nox1 and iNOS induction, and is independent of blood pressure and serum lipids.